IMMUNOHISTOCHEMICAL CHARACTERISTICS OF THYROID GLAND CHANGES IN PATIENTS WITH AUTOIMMUNE THYROIDITIS - Sadikhov, F.G. (World of Medicine and Biology, 2023)
The purpose of the study was to perform an immunohistochemical study of autoimmune changes in the thyroid gland in autoimmune thyroiditis patients who received various treatment methods. In the main group, immunohistochemical studies were performed on 30 patients. The control group consisted of six patients in whom the histochemical examination was performed postmortem. Statistically significant differences were found between the forms of autoimmune thyroiditis according to Ki–67(+) (F=1428.687, p
Keywords: autoimmune thyroiditis; thyroglobulin; proliferative activity; biomarker; immunohistochemical studies